Job Characteristics, Job Involvement, and Transformational Leadership’s Effects on Employee Performance through Work Engagement - Rizyana Mirda; Prasetyo Prasetyo (International Journal Labs, 2022)
The conditions of employee performance in a company is inseparable from several factors that can influence it. Job characteristic, job involvement, and leadership are things that can affect employee performance. But they do not necessarily directly affect an employee's performance, and there can be factors that bridge them so that employee performance gets better. This research is to prove and analyze the influence of Job Characteristics, Job Involvement, Transformational Leadership on Work Engagement and Performance on Bank Jatim employees, and to prove and analyze the influence of Work Engagement on Performance on Bank Jatim employees. The sample population is 365 employees of Bank Jatim. The source of data in this study collected by survey method. Data analysis techniques used in research using SEM with Smart PLS software.The results of the analysis can be concluded that Job Characteristic, Job Involvement, Transformational Leadership has a significant and positive influence on Work Engagement and Job Involvement has a significant and positive influence on employee performance of Bank Jatim employees, but Job Characteristic and Transformational Leadership has no significant and positive influence on Employee Performance Bank Jatim employees, while Work Engagement has a significant and positive influence on employee performance of Bank Jatim employees.